Adult asthma assessment in an accident & emergency department. - Coonar, A S (1994)
Poor initial assessment contributes to morbidity and mortality in acute severe asthma. We have audited this aspect of management in an A & E department over a single 6-month senior house officer employment cycle. The use of a cheap and simple stamp highlighting important clinical features of asthma was associated with a significant improvement in early assessment.